2017
DOI: 10.3390/rs9121247
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Land Surface Temperature from Feng Yun-3C/MERSI Data Using a New Land Surface Emissivity Scheme

Abstract: Land surface temperature (LST) is a key parameter for a wide number of applications, including hydrology, meteorology and surface energy balance. In this study, we first proposed a new land surface emissivity (LSE) scheme, including a lookup table-based method to determine the vegetated surface emissivity and an empirical method to derive the bare soil emissivity from the Global LAnd Surface Satellite (GLASS) broadband emissivity (BBE) product. Then, the Modern Era Retrospective-Analysis for Research and Appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 64 publications
(84 reference statements)
0
20
0
Order By: Relevance
“…As described in Section 2.2, GAPRI atmospheric profiles were used to derive the coefficients of the algorithms, whereas the Cloudless Land Atmosphere Radiosounding (CLAR) [57] with 382 profiles, Thermodynamic Initial Guess Retrieval (TIGR) [58] with 946 profiles, and 2762 SeeBor V5.0 global profiles (hereafter SeeBor) [59] were used for validation purposes. All the profiles are restricted to land under clear sky conditions [60] based on the method of Galve et al [57]. To improve the inversion accuracy of the land surface temperature, the coefficients of the enterprise algorithm were fitted based on the water vapor content, as shown in Table 2.…”
Section: Algorithm Coefficientsmentioning
confidence: 99%
“…As described in Section 2.2, GAPRI atmospheric profiles were used to derive the coefficients of the algorithms, whereas the Cloudless Land Atmosphere Radiosounding (CLAR) [57] with 382 profiles, Thermodynamic Initial Guess Retrieval (TIGR) [58] with 946 profiles, and 2762 SeeBor V5.0 global profiles (hereafter SeeBor) [59] were used for validation purposes. All the profiles are restricted to land under clear sky conditions [60] based on the method of Galve et al [57]. To improve the inversion accuracy of the land surface temperature, the coefficients of the enterprise algorithm were fitted based on the water vapor content, as shown in Table 2.…”
Section: Algorithm Coefficientsmentioning
confidence: 99%
“…In these years, space-based methods, like radio occultation and microwave satellite-borne passive microwave detectors, provide availability to measure meteorology parameters and PWV distribution from space [3,17,18]; they have lots of advantages compared to ground observation methods. Like RO, it has high vertical resolution and RO measurements are not significantly affected by clouds and precipitation [19][20][21][22]; besides, its observation coverage is global, not a matter of land or ocean area, so radio occultation is applied to obtain PWV in a global area under allweather conditions [23][24][25]. Precision statistical related studies reveal over ocean-dominated geographical areas; PWV retrieved from RO and ground-based GNSS exhibits a global mean difference of around 1 mm, a root-meansquare deviation of about 5 mm, and a correlation above 0.9 [26].…”
Section: Introductionmentioning
confidence: 99%
“…Windahl et al [54] indicated that the overall LST RMSE retrieved from radiative transfer equation method for all Landsat datasets were 0.44 K larger than those values for the cloud-free Landsat dataset. Meng et al [44] also indicated the LST calculated from the radiative transfer equation method was underestimated when the study area was covered by clouds.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The estimated LSTs determined using the RTE method were evaluated with the ground measurements from six in situ sites during the Heihe Watershed Allied Telemetry Experimental Research (HiWATER) experiment [43]. There were two in situ sites over the vegetation surfaces and four in situ sites over bare soil, and detailed information about the in situ sites can be found in Meng et al [44]. The land surface emissivity were determined using the method proposed by Meng et al [8], which used the ASTER Global Emissivity Dataset (GED) and Vegetation Cover Method (VCM) to improve land surface emissivity accuracy.…”
Section: Real Datamentioning
confidence: 99%